Geothermal characteristics and high-yield geothermal well parameters in the Baimiaozi sag of Huhe depression - Zhanxiong MA; Fugui YAN; Ming LI; Qing ZHANG; Jing HAN; Junbin ZHAO (Shuiwen dizhi gongcheng dizhi)
The geothermal geological conditions of Baimiaozi sag in Huhe depression are favorable for geothermal exploration. Previous geothermal investigations primarily focused on boreholes around the northern shallow-buried zone of the sag center, where the thermal reservoirs are shallow and relatively thin. However, exploring deep Neogene sandstone geothermal reservoirs in the southwest of the sag represents a key direction for geothermal exploration and development in Hohhot. Based on the borehole TD1 in the southwest of Baimiaozi sag, this study analyzed the seismic data by interpretation of two dimension seismic profile, drilling, geophysical logging, blowout test, and water sample test, to study the characteristics, deep thermal convection mechanism, and main parameters of the Neogene geothermal reservoir. The results show that the Neogene geothermal reservoir in the southwest of the sag is thick, which is a favorable target for exploration and development of geothermal resources. The deep Neogene geothermal reservoir in borehole TD1 is composed of a considerable thickness of conglomeratic sandstone, with a total thickness of 299.5 m, accounting for 40.69% of the total thickness of the formation. 14 geothermal reservoir layers have been developed in the Neogene Miocene from 2030.9 m to 2282.5 m deep in TD1 borehole, with a total thickness of 160.4 m, accounting for 63.75% of the formation’s total thickness and an average porosity value of 26.27%, which is the dominant water-yielding section of the borehole TD1. The wellhead temperature in the borehole TD1 is 75.0 °C, and the max bottom temperature is 80.7 °C. The geothermal gradient from 2030.9 m to 2282.5 m with high porosity development is significantly lower, suggesting the existence of deep heat convection. The pumping test in borehole TD1 demonstrates the reservoir’s high water yield, with a stable well flow rate of 233.12 m3/h. The heating potential with the single well is estimated at 33×104 m2, making it the highest-yielding geothermal well currently discovered in the Huhe depression. These findings highlight the characteristics of high-yield thermal storage and the single-well heating potential of the Neogene geothermal reservoir in the southwest of Baimiaozi sag, providing valuable insights for the future exploration and development of high-yield geothermal resources in the Huhe depression.